The Influence of a Novel Inorganic-Polymer Lubricant on the Microstructure of Interstitial-Free Steel during Ferrite Rolling - Ning Kong; Jie Zhang; Hongbo Li; Boyu Wei; David R. G. Mitchell (Metals, 2020)
A novel polyphosphate lubricant was used and evaluated during hot (ferrite) rolling of an interstitial-free (IF) steel. The texture evolution of these rolled IF steels have been examined by means of X-ray diffraction (XRD) and electron backscatter diffraction (EBSD) measurements. The polyphosphate lubricant shows an improved lubrication performance in terms of the texture optimization compared with lubricating oil and with unlubricated conditions. The γ-fiber texture is enhanced, and less shear texture is produced. This microstructure is responsible for enhanced drawability of ferrite rolled IF steels. The very high thermal stability of the polyphosphate enabled its use at very high temperatures (from 700 to 800 °C). Rolling temperature exerted limited influence on the resulting rolling texture evolution. The polyphosphate lubricant stabilizes the surface texture and reduces the gradient of shear texture through the thickness. The in-grain shear bands are reduced significantly (48.5%) compared with the unlubricated condition. Measured grain orientations indicate that the favorable texture of {111}<112> along the γ-fiber is developed while the undesired α-fiber texture of {001}<110> is effectively suppressed.